2007
DOI: 10.1080/10929080701336207
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopic navigation system for hip surface replacement

Abstract: Metal-on-metal hip resurfacing arthroplasties represent an alternative to total hip arthroplasties for young and active patients, enabling the preservation of intact femoral bone and therefore improving the prognosis for future hip joint replacements. Follow-up studies have shown that the main reasons for early implant failure are mal-orientation of the implant stem in relation to the femoral neck axis, and notching of the femoral neck during femoral head preparation, as well as by exposed cancellous bone afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
0
16
0
3
Order By: Relevance
“…Recent cadaveric and sawbone studies suggest using navigation for HR is more accurate [14,26]. Similar conclusions have been reported in smaller clinical studies using fluoroscopic guidance or fluoroscopic-based surgical navigation [7,17,20].…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Recent cadaveric and sawbone studies suggest using navigation for HR is more accurate [14,26]. Similar conclusions have been reported in smaller clinical studies using fluoroscopic guidance or fluoroscopic-based surgical navigation [7,17,20].…”
Section: Introductionmentioning
confidence: 56%
“…A cadaveric study also found, when aiming for a predetermined stem-shaft angle of 135°, the mean stemshaft angle obtained by conventional instrumentation was 127.7°(range, 120°-132°) compared with 133.3°(range, 131°-139°) in the computer navigation group [14]. Accuracy of guide wire placement also has been improved by using either fluoroscopic guidance [26] or fluoroscopicbased surgical navigation [7,17].…”
Section: Discussionmentioning
confidence: 96%
“…Mithilfe der hier durchgeführten Anatomiestudie sollte zum einen die C-Arm-Navigation beschrieben werden und zum anderen die Effizienz und Genauigkeit dieses Systems bei Anwendung überprüft und beurteilt werden. Insbesondere auf dem Gebiet der navigierten Chirurgie werden seit Längerem neben fluoroskopischen und CT-basierten Navigationssystemen bildlose Verfahren propagiert [14,15] Bei Vorhandensein einer Echtzeitansicht eines benötigten Rönt-genbilds kann diese Ansicht durch den Anwender vor Bilderstellung optimiert werden, was zeitintensiv sein kann. Außerdem muss hier darauf hingewiesen werden, dass sämtliche Operateure noch keine hinreichende Erfahrung mit Navigationssystemen besitzen.…”
Section: Auswertungunclassified
“…Die Effizienz und der Erfolg fluoroskopischer Systeme hängen zu einem großen Teil von der Qualität der zugrunde liegenden multiplanaren Röntgenbilder ab. Theoretische Analysen haben gezeigt, dass zusätzlich zum optimalen Sichtfeld der erzeugten Aufnahmen die relative Orientierung multiplanarer Röntgenbilder einen großen Einfluss auf die zu erwartende Genauigkeit der Navigation hat [8,9]. So ist bei der Navigation in 2 Röntgenbildern bei orthogonaler Ausrichtung zueinander mit dem kleinsten Fehler zu rechnen, während bereits bei einem Winkelunterschied von nur 60°bereits mit einem um 40 % größeren Fehler zu rechnen ist.…”
unclassified
“…Hess et al [27] reported the first use of 2D fluoroscopy to navigate the femoral head for hip resurfacing. Belei et al [8] presented an alternative method for 2D fluoroscopy. With the increase in 3D imaging technologies, Hodgson et al [28] presented using computed tomography (CT) for resurfacing navigation.…”
Section: Introductionmentioning
confidence: 99%